PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN di RSUD H. ANDI SULTHAN DAENG RADJA KAB. BULUKUMBA - Haerani; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2017)
The phenomenon that is happening now is that many nurses pay little attention to safety and comfort and are not concerned with patient complaints so that patients are less satisfied in the nursing services provided. This study aims to determine the relationship of nurses caring behavior with the level of patient satisfaction in the Seruni care room at H. A. Sulthan Hospital Dg Radja Bulukumba Regency. This type of research is an analytic observational study with a